A comunidade que foi: resenha do livro "Being with the Dead", de Hans Ruin - Araújo, Pedro Igor (Ekstasis: Revista de Hermenêutica e Fenomenologia, 2023)
Resenha do livro: RUIN, H. Being with the Dead: Burial, Ancestral Politics, and the Roots of Historical Consciousness. Stanford, California: Stanford University Press, 2018.